KOLABORASI MAHASISWA UNIBA DALAM EDUKASI GIZI, LITERASI KARAKTER, DAN ANTI-BULLYING DI SDN 1 DALUNG: MODEL PEMBERDAYAAN BERBASIS SEKOLAH DASAR - Nurhildayanti, Siti; Lutfiah, Ismi Nur; Wafiroh, Wafiroh; Sastra, Wira; Sukriyah, Sukriyah; Anugrah, Akmal; Puspa, Rani (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The challenges of literacy, nutrition, and bullying cases in elementary schools are strategic issues in shaping children’s character from an early age. The community service program conducted by the KKM Group 03 of Universitas Bina Bangsa (UNIBA) aimed to enhance the awareness and understanding of SDN 1 Dalung students regarding balanced nutrition, character values, and the creation of a child-friendly school environment. The activities applied a participatory educational approach using storytelling, simulations, and educational games. The program involved collaboration among students from various study programs, field supervisors, school teachers, and police resource persons. Evaluation results indicated a significant improvement in students’ understanding of balanced nutrition, character literacy, and anti-bullying attitudes. This community service model proved effective as an elementary school-based empowerment method and could be replicated in similar educational contexts.